Role of MRI Diffusion Tensor Imaging in the Assessment of Traumatic Spinal Cord Injuries. - Suha Raheem Hilal; Dr. Samah Dhahir Jalood Hachami; Khaleel Ismael Al-hashimi (Zien Journals, 2023)
Traumatic spinal cord injury (SCI) is a severe condition that significantly affects a patient's physical, psychological, and social well-being. According to estimates, there are 11 to 53 new instances of SCI for every million people
Keywords: FA; Traumatic spinal cord injury; MRI Diffusion Tensor Imaging